Tinjauan Penggunaan Obat Tetes Mata Antibiotik Periode Januari-Maret 2021 di Balai Kesehatan Mata Pontianak - Husnani Husnani (Jurnal Rumpun Ilmu Kesehatan, 2023)
Infectious diseases are still an important public health problem, especially in developing countries. One of the mainstay drugs to overcome this problem is antibiotics. Bacterial resistance to antibiotics continues to increase throughout the world, including Indonesia. The purpose of this study was to determine the average use of antibiotic eye drops for the period January to March 2021 at the Community Eye Health Center January to March 2021. The method in this research is a descriptive survey. The population in this study were all prescription data from January to March at the Community Eye Health Center. Results In January to March 2021 the average number of uses of the antibiotic Levofloxacin was 39.6. Polynel is 35. Bralifex is 34.